A Constitutive Model for Yield Strength and Work Hardening Behaviour of Aluminium Alloys during Artificial Ageing - Kang Ji (Metals, 2020)
In this study, a unified constitutive model has been developed for both yield strength and work hardening behaviour prediction of aluminium alloys with different types of precipitates during and after artificial ageing. The different type and dimensions of general precipitate shapes (sphere, plate, rod) have been classified and modelled by a primary dimension and aspect ratio, with which a general set of equations has been utilised to model the precipitates evolutions during ageing of various aluminium alloys. In addition, the effects of main microstructures on not only yield strength but also work-hardening behaviour of artificially aged aluminium alloys have been considered and modelled, based on which, a whole set of unified constitutive model considering both micro- and macro-properties for long-term artificial ageing of aluminium alloys has been proposed. Artificial ageing of two representative aluminium alloys (an Al-Mg-Si alloy AA6063 and an Al-Cu-Li alloy AA2198) has been adopted to show the capability and effectiveness of the developed model. The results show that the model can successfully predict the microstructures, yield strength and work hardening behaviour of various aluminium alloys with different precipitate types after long-term artificial ageing process, e.g., from 0 h to 500 h. It is believed that the model can be used for ageing of other aluminium alloys with dominant sphere, plate or rod-shaped precipitates.